2023
DOI: 10.3390/s23041851
|View full text |Cite
|
Sign up to set email alerts
|

Eye Recognition by YOLO for Inner Canthus Temperature Detection in the Elderly Using a Transfer Learning Approach

Abstract: Early detection of physical frailty and infectious diseases in seniors is important to avoid any fatal drawback and promptly provide them with the necessary healthcare. One of the major symptoms of viral infections is elevated body temperature. In this work, preparation and implementation of multi-age thermal faces dataset is done to train different “You Only Look Once” (YOLO) object detection models (YOLOv5,6 and 7) for eye detection. Eye detection allows scanning for the most accurate temperature in the face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In the scenarios mentioned in Section 3.1, spam detection stands out as a specific case. Certain studies have employed complex models to extract textual features from emails [11,38]. However, these methods frequently encounter challenges in capturing the interrelations between emails and demand domain-specific knowledge.…”
Section: Edgesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the scenarios mentioned in Section 3.1, spam detection stands out as a specific case. Certain studies have employed complex models to extract textual features from emails [11,38]. However, these methods frequently encounter challenges in capturing the interrelations between emails and demand domain-specific knowledge.…”
Section: Edgesmentioning
confidence: 99%
“…To ensure effective filtering of adjacent edges, we introduce the convolution parameter penalty based on node similarity, which is denoted by 𝛽 in Equations ( 10) and (11). This allows the representations of edges connecting similar types of nodes to fuse more quickly, thereby facilitating the identification of localized anomalies.…”
Section: Adjacent Edge Weightsmentioning
confidence: 99%
“…Almeida et al compared several ML classifiers and found SVM performed well, however, they only used word frequency as a feature and did not evaluate DL models [4], [41]. Similarly, Gupta et al compared 8 ML clas- 747 [32], [33], [7], [34], [35] NUS SMS Corpus [31] 2015 67,063 Nil [36], [37], [38] SpamHunter [14] 2022 25,889 947 [39], [40] sifiers, including SVM and CNN, using only TF-IDF features and only evaluated conventional ML and one DL classifier [6]. Roy et al [42] compared CNN and LSTM with traditional two-class classifiers for SMS spam detection using multiple model stack structures and found that CNN and LSTM performed better.…”
Section: Sms Spam Datasetsmentioning
confidence: 99%